An Analysis of Positive Politeness in Wicked 2024 Focusing on Main Characters - Yunita Pingky Setiawati; I Gusti Ayu Vina Widiadnya Putri (Universitas Islam Negeri Palopo, 2025)
This study analyzes the use of positive politeness strategies employed by the main characters, Elphaba and Glinda, in the 2024 film adaptation of Wicked. Using a descriptive qualitative approach, the data consist of 14 selected utterances taken from the film’s official English subtitles, which yielded 19 instances of positive politeness strategies. The analysis applies Brown and Levinson’s (1987) politeness framework. The findings reveal that seven types of positive politeness strategies were used, with Strategy 15 (Giving gifts to the hearer) appearing most frequently (5 occurrences or 26.3%), followed by Strategy 1 (Noticing the hearer’s needs), Strategy 2 (Exaggeration), and Strategy 6 (Avoiding disagreement), each occurring three times (15.8%). These strategies predominantly occur in emotionally charged interactions where the characters attempt to build solidarity, reduce tension, and maintain interpersonal harmony. The findings demonstrate that positive politeness in Wicked functions not only as a linguistic tool for maintaining social relationships but also as a narrative device that reflects character development within a musical-fantasy cinematic context, where dialogue and emotional expression are closely intertwined. This study contributes to pragmatic studies by providing empirical evidence of how politeness strategies operate in film discourse, particularly within dramatized and performative genres.